Fee Based Income dalam Perspektif Fikih ‎Muamalah - Imam Buchori (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2010)
There are two banking bankings in indonesia, interest-based banking and shariah-compliant banking. Interest-based banking has been around ever since before the independence of Indonesia in 1945. In contrast, shariahcomliant baking emerged only in 1990an. In reality, the two systems are contradictory, bacause in interest-based banking, interest is instrumental in its operation. In contrast, shariahcompliant banking use profit sharing instead. Both banking systems are companies which operate in three main banking -related activities; funding, lending, and services. Service is intended to support the two main banking products of lending and funding. Thus, the purpose of service activity is to facilitate available banking services. The revenue of these banking services is generated from administration fee, comission, rent, and other expenses. The revene of service in banking industry is called fee based income which is categorized in islamic jurisprudence as ujrah or fee according to a fatwa of National Shariah Board of Indonesian Ulama Council.